2010
DOI: 10.1175/2010jcli3592.1
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetry in the Duration of El Niño and La Niña

Abstract: El Niño and La Niña are not a simple mirror image, but exhibit significant differences in their spatial structure and seasonal evolution. In particular, sea surface temperature (SST) anomalies over the equatorial Pacific cold tongue are larger in magnitude during El Niño compared to La Niña, resulting in positive skewness of interannual SST variations. The associated atmospheric deep convection anomalies are displaced eastward during El Niño compared to La Niña because of the nonlinear atmospheric response to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
247
1
2

Year Published

2014
2014
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 339 publications
(274 citation statements)
references
References 82 publications
24
247
1
2
Order By: Relevance
“…These composite analyses shown in Fig. 1 are in broad agreement with those reported by Okumura and Deser (2010), where a different atmospheric reanalysis product was used.…”
supporting
confidence: 88%
See 2 more Smart Citations
“…These composite analyses shown in Fig. 1 are in broad agreement with those reported by Okumura and Deser (2010), where a different atmospheric reanalysis product was used.…”
supporting
confidence: 88%
“…It is generally accepted that there is an asymmetry in the duration of the two phases of ENSO events, with La Niña events lasting longer than El Niño events (Larkin and Harrison 2002;McPhaden and Zhang 2009;Obha and Ueda 2009;Okumura and Deser 2010;Okumura et al 2011;DiNezio and Deser 2014). Given that McGregor et al (2013) proposed that the asymmetries in the southward wind shift (e.g., El Niño event magnitude is strongly related to the extent of the meridional wind movement, while the meridional wind movement during La Niña events remains relatively small The boxplots in Fig.…”
Section: Duration Asymmetrymentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies suggested that the genesis of an extreme El Niño could be attributed to the effects from nonlinear convection (Hoerling et al, 1997;Kang and Kug, 2002), biological feedback (Timmermann and Jin, 2002;Marzeion et al, 2005), tropical instability waves (Vialard et al, 2001), and the feedback form the Indian Ocean (Okumura and Deser, 2010). However, as found in this study, the genesis and development of extreme El Niño events are closely associated with WWB and the variation of the upper ocean heat content.…”
Section: Discussioncontrasting
confidence: 44%
“…Oceanic nonlinear advection does not appear essential for the onset of strong EN. The threshold convective response to SST (Ohba and Ueda 2009;Dommenget et al 2012;Choi et al 2013), state dependent noise acting under EN favorable conditions (Lengaigne et al 2004;Jin et al 2007), all potentially producing asymmetric features of ENSO, like its skewness, the asymmetric time evolution of strong EN and La Niña (LN) event (Ohba and Ueda 2009;Okumura and Deser 2010) or the asymmetric pattern of the zonal wind stress along the equator (Kang and Kug 2002). Note that the study of ENSO nonlinearities has been mostly oriented towards explaining the aforementioned statistical features of ENSO, rather than focusing on the development phase of the strong warm events, which could convey other insights on their dynamics and predictability.…”
Section: Introductionmentioning
confidence: 99%